Marketing Strategies to Increase Number of Visitors (Case Study: Karang Setra Swimming Pool) - Hermawan, Melina; Sitinjak, Nova Yanti (Zenit, 2014)
Bandung is one of popular places of interest in Indonesia. Karang Setra Swimming Pool is one of the recreational swimming pools in Bandung. It provides a water park and it has a strategic location in the north of Bandung at Jalan Karang Setra. The mananagement of Karang Setra Swimming pool wishes to have a rising revenue every year, but since 2009 to 2012 the company has suffered from an average of 52.56 % fall in their revenue. The cause of the declining revenue issuspected from customer dissatisfaction and from unidentified factors which cause consumers to choose a particular swimming pool. The methodology uses consumer satisfaction survey to find the strengths and weaknesses of Karang Setra Swimming Pool compared to its competitors (Taman Graha Melati Swimming Pool and Tirtamulya Swimming Pool). The analysis method uses Importance Performance Analysis and Hypothesis Test of Customer Dissatisfaction. The result shows that the variable which dissatisfies the customers and even becomes Karang Setra’s weakness is the slippery ceramics in the swimming pools and the ticket price considered “high” compared to the cleanliness of the swimming pools. The suggested positioning is a recreational water park with aspecial price for groups, while the proposed market target is middle to lower class customers.Keywords: Hypothesis Test of Customer Dissatisfaction, Importance Performance Analysis